The Local Wisdom of Mathematical Language of Malay Community of Pangkalpinang: An Ethnographic Study - Yudi Yunika Putra; Sasih Karnita Arafatun (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2024)
Pangkalpinang is the capital of Bangka Belitung Province by occupied most Melayu people with a rich culture. There are a number of cultures Pangkalpinang public relates to context learning mathematics. However, not many of the teachers in Pangkalpinang apply culture in learning mathematics. Whereas culture can be a starting point in learning mathematics. So the aim of the research for explore local wisdom quantity mathematics language public melayu Pangkalpinang which can used starting point in learning mathematics. The research used an exploration method with an approach of ethnography sourced from a literature review, field observation, and interviews with elders or the public who live in the area research place. Analysis of data through reduction data, presentation data, and concluding. The stages of research with a beginning observation about the context of public culture who made starting point learning. The next is the research theme which explores the language culture melayu Pangkalpinang public with related ethnomathematics, the next determine data source, data collection, analysis data, and drafting report and reflection. The result of the research shows that there is a quantity of language mathematics used by the Pangkalpinag public, and that matter can become a starting point in learning mathematics. Quantity language covers units, tens, twenties, hundreds, thousands, tens of thousands, hundreds of thousands, and millions, and also produces fractional numbers and indefinite numbers.